"Simply Speaking Your Mind, from the Depths of Your Soul": Therapeutic Factors in Experiential Group Psychotherapy for Sex Offenders. Issue 3 (26th May 2016) - Willemsen, Jochem; Seys, Valerie; Gunst, Ellen; Desmet, Mattias
ABSTRACT: Sex offenders demonstrate heightened levels of negative emotions, traumatic experiences, mental health issues, and emotion disregulation. This study presents a qualitative analysis of interviews with sex offenders concerning helpful experiences in experiential group psychotherapy. Experiential group psychotherapy aims to increase emotional awareness, emotional expression, and reflection on emotions. The data were thematically coded according to Yalom's therapeutic factors for group psychotherapy. The results indicate that Cohesion is reported to be most helpful: when clients trust their peers and feel respected by therapists, emotional engagement in treatment is achieved. Clients report being more capable of focusing on and tolerating their own emotions, which also influences the way they relate to other people (Interpersonal Learning). Experiences related to Universality, Instillation of Hope, Altruism, and Existential Learning were also mentioned as helpful in the treatment.